The status of the hawksbill Eretmochelys imbricata and green turtle Chelonia mydas of Melaka and Negeri Sembilan [Malaysia] - Mortimer, J.A. (Florida Univ., Gainesville, Florida (USA). Dept. of Zoology) (2013)
In this paper we present our assessment of the importance of the sea turtle nesting and foraging habitats of the states of Melaka and Negeri Sembilan. Our studies done in 1990 and 1991 revealed that the population of the highly endangered hawksbill turtle Eretmochelys imbricata nesting in the state of Melaka is in fact the largest in Peninsular Malaysia. The duration of the breeding season was also established for the first time: it extends from February through September, and peaks during May, June and July. In 1990, the Department of Fisheries and the state of Melaka, with assistance from WWF Malaysia, established a hatchery near Pengkalan Balak to which collectors sold their eggs during part of the 1990 and all of the 1991 nesting seasons. Of the 324 egg clutches recorded in 1991 (certainly an underestimate of the total actually laid), 69 were deposited on mainland beaches between the northern border of Melaka and Kem Terendak, 26 on Pulau Upeh, and 5 near Tanjung Kling. Further surveys are needed to confirm reports of important nesting activity on islands adjacent to Pulau Besar, especially Pulau Nangka. Our surveys and interviews indicate that significant numbers of juvenile and adult hawksbill and green turtles Chelonia mydas inhabit foraging grounds in the Straits of Melaka. Conservation efforts must focus on preservation of critical nesting and foraging habitat, complete protection of turtle eggs, and prevention of accidental captures of turtles in fishing gear. We suggest that Pulau Upeh be designated a turtle nesting sanctuary